54.5k views
0 votes
Solve: x2 − x − 6 x2 = x − 6 2x + 2x + 12 x After multiplying each side of the equation by the LCD and simplifying, the resulting equation is

User Smu
by
5.6k points

2 Answers

0 votes

What are the solutions to the equation?

A. x = -6 and x = -2/3

Explanation:

this was a second part to the question for me so i decided to give u guys it as well, incase u come across it

User Petrusion
by
5.7k points
6 votes

Answer:

C) 3x^2 + 20x + 12 = 0

Step-by-step explanation: Because it is the right answer


User Victor Nazarov
by
6.5k points